Current state of knowledge on the potential and production of Cucurbita moschata (pumpkin) in Africa: A review - Gbemenou, Ulrich Herbert; Ezin, Vincent; Ahanchede, Adam (My University, 2022)
Pumpkin has high nutritional value essential for food security. Despite many benefits, it still considered an orphan crop in Africa. Very little information is available on the potential and production of pumpkin in Africa due to neglect by researchers and improvement program. Classical research, both theoretical and empirical, was used to conduct a systematic review of the various result trends obtained by researchers in relation to the topic. Using Google Scholar, relevant literature was selected, analyzed and summarized. In Africa, the fruit, seeds and leaves of the pumpkin is consumed. This dietary diversity of pumpkin could contribute to the improvement of people's livelihoods. Countries such as Morocco, South Africa and Tunisia are making considerable profits from the export of pumpkin. However, its production is very low because its potential is not fully exploited. In this context, research and development strategies must be put in place so that pumpkin becomes part of the African diet. The diversity, origins and distribution, utilization patterns, relative importance, production and bottlenecks of pumpkin in Africa are reviewed. These results can be used as a basis for further research on yield improvement and pest management.
Keywords: Africa; bottlenecks; food security; orphan crops; pumpkin